PENGEMBANGAN METODE PENENTUAN NITRIT PADA BAYAM MENGGUNAKAN REAKSI DIAZOTASI - Painer Siregar, Fately
Nitrites may naturally present in vegetables consumed by human such as spinachs and lettuces. This substance could cause intoxication when presentsat high concentration. The toxic effect of nitrite is due to its capability of binding haemoglobin in blood so that it impairs blood capability to bind oxygen. The determination of nitrite is commonly performed by means of spectrophotometric method applying Griess reagent, which based on diazotation reaction. The aim of this research was to develop an alternative method for determination of nitrite in vegetables, especially spinach. The method was also based on diazotation and coupling reactions, but instead of sulfanilic acid and N-(1-naphtyl)ethylenediamine dihydrochloride, sulfanilamide and 2-naftol were used. Sulfanilamide will form diazonium salt and will be coupled by 2-naphtol.Spinach samples may contain nitrite were extracted by being blended in water as its solvent, then it was acidified with hydrocloric acid forming nitrite acid. Nitrite acid formed was reacted by sulfonilamide forming diazonium salt. Diazonium salt formed then was coupled with 2-naphtol at pH 9.0. The absorbance of the solution was measured at 387 nm. This method gave linear calibration curve in the concentration range of 10 to 100µg/mL with a regression equation of Y = 0.0131X + 0.0254 and r 2 = 0.993.The recovery of nitrite at the concentration levels of 10, 50 and 90µg/mL were respectively determined using standard addition method and found to be 103.33, 92.12 and 92.2%. Based on these results, it was concluded that this method was suitable to be applied as alternative method for the determination of nitrite in spinach.